RNA interference-mediated suppression and replacement of human rhodopsin in vivo. - HUMPHRIES, MARIAN; HUMPHRIES, PETER; FARRAR, GWYNETH JANE (Elsevier, 2007)
Mutational heterogeneity represents a significant barrier to development of therapies for many dominantly inherited diseases. For example, >100 mutations in the rhodopsin gene (RHO) have been identified in patients with retinitis pigmentosa (RP). The development of therapies for dominant disorders that correct the primary genetic lesion and overcome mutational heterogeneity is challenging. Hence, therapeutics comprising two elements?gene suppression in conjunction with gene replacement?have been investigated. Suppression is targeted to a site independent of the mutation; therefore, both mutant and wild-type alleles are suppressed. In parallel with suppression, a codon-modified replacement gene refractory to suppression is provided. Both in vitro and in vivo validation of suppression and replacement for RHO-linked RP has been undertaken in the current study. RNA interference (RNAi) has been used to achieve 90% in vivo suppression of RHO in photoreceptors, with use of adeno-associated virus (AAV) for delivery. Demonstration that codon-modifed RHO genes express functional wild-type protein has been explored transgenically, together with in vivo expression of AAV-delivered RHO-replacement genes in the presence of targeting RNAi molecules. Observation of potential therapeutic benefit from AAV-delivered suppression and replacement therapies has been obtained in Pro23His mice. Results provide the first in vivo indication that suppression and replacement can provide a therapeutic solution for dominantly inherited disorders such as RHO-linked RP and can be employed to circumvent mutational heterogeneity.
PUBLISHED
Keywords: Genetics